PENGARUH KECERDASAN EMOSIONAL TERHADAP PENYESUAIAN PERKAWINAN PADA USIA DEWASA AWAL - Wening Pusparini (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2017)
ABSTRACT The objective of this study is to determine the effects of emotional intelligence on marital adjustment in early adulthood. The study was conducted in South Jakarta. The population of this study is the early adulthood resident of district Pela Mampang, South Jakarta . Total population is about 500 people and the researchers took 46 people as the sample in this study because they meet the study requirement. This study used a quantitative approach. The method used in this study is ex post facto. And the sampling technique is probability sampling.The type of probability sampling that is used in this study is purposive sampling, whereas the sampling technique depends on the criteria. Data collection technique used emotional intelligence and marital adjustment scale. The analytical techniques used in this study is normality test, linear test, and regression analysis. Based on the study result, F = 275 912, p = 0.00 <0.05 (significant), suggested that there is a significant influence between emotional intelligence on marital adjustment in early adulthood. The regression equation was Y = 25 276 +0249 X. This regression suggested that if emotional intelligence is 0, then the adjustment is positive 25,769. Regression coefficient of emotional intelligence variable is 0.249 which means if emotional intelligence scores is increased, then the marital adjustment will increase 0.249. We obtained a positive relationship between emotional intelligence and marital adjustment because the coefficient is positive. This means that, higher emotional intelligence will result on higher marital adjustment. The influence of emotional intelligence variables on marital adjustment in early adulthood that is obtained by Adjusted R Square is 0859 which means emotional intelligence affect marital adjustment in early adulthood couples by 85.9%, while the remaining percentage showed that there are other factors that influence marital adjustment on early adulthood beside emotional intelligence. Keywords: Emotional intelligence, Marital adjustment